THE RELATIONSHIP BETWEEN KNOWLEDGE AND COMPLIANCE WITH BLOOD ADDED TABLETS IN ADOLESCENT WOMEN - Hesta Yuniartanti Putri; Lilik Djuari; Euvangelia Dwilda (UNIVERSITAS AIRLANGGA, 2023)
The incidence of anemia in Indonesia is still quite high in 2013 at 37.1% and increased to 48.9% in 2018. Efforts to prevent nutritional anemia among adolescents are still low, based on the coverage figures for blood supplement tablets (TTD) received by adolescents daughter by 76.2%. However, only 1.4% took iron tablets as recommended.This research aims toto analyze the relationship between knowledge and adherence to taking iron tablets in young women.The research method uses observational analytic with a cross sectional approach. The sample in this study were female adolescents at SMP Negeri 1 Purwoasri who were included in the inclusion criteria and were determined using a simple random sampling technique. Retrieval of data through primary data and secondary data. Primary data was obtained by filling out a questionnaire about knowledge of blood supplement tablets filled out by young women. While the secondary data is in the form of data on the number of young women who received iron tablets and consumed iron tablets. Research data were analyzed using the chi-square test. The research results showmost of the respondents had sufficient knowledge, namely 57 respondents or 75%. There were 14 respondents (18.4%) with poor knowledge and 5 respondents (6.6%) with good knowledge. There were 29 respondents (38.2%) who were not compliant in consuming blood supplement tablets with sufficient knowledge category. The results of bivariate analysis with the Chi-Square test obtained p =0.001.The data shows that there is a significant relationship betweenknowledge with adherence to taking iron tablets in young women.